The COVID-19 Pandemic and Haiti's Changing Remittance Landscape - Cela, Toni (2022)
In 2020, analyses from multilateral institutions predicted that the COVID-19 pandemic would hamper remittance transfers to the Latin America and Caribbean region; yet they showed steady increases in 2020 and 2021. Haiti’s remittance economy has largely maintained its vitality, helping families weather multiple crises. Drawing on data from a study of the impact of COVID-19 on Haitian households and remittance data from Haiti’s Central Bank, this article examines Haiti’s changing remittance landscape, with particular attention paid to new migratory flows to Latin America that have emerged since the January 2010 earthquake. Considering the increase in migration to Brazil and Chile, among other countries, between 2010 and 2020, we ask, what role have remittances from South America played in Haitian households leading up to and during the COVID-19 pandemic?